Aerobic bacterial flora of normal human conjunctiva (Journal of Dhaka National Medical College & Hospital, 2013)
Background and purpose: The conjunctiva as a mucus membrane sustains permanent flora of indigenous bacteria which plays an important role to maintain normal conjunctival function. This study was carried out to see the pattern of conjunctival bacterial flora in healthy individuals.Methods: This prospective cross sectional study was carried out in Bangabandhu Sheikh Mujib Medical University during the period of January 2011 to December 2011. Total 400 conjunctival swabs were collected from both eyes of 200 healthy individuals those attending the Eye Out patient department (OPD) of BSMMU with complaints other than eye infections and their attendants.Results: Out of 400 swabs, 95 (23.75%) culture was positive in healthy individuals. Staphylococcus epidermidis (65.26%) was the predominant organism followed by Moraxella sp. and Pseudomonas sp. (7.37%). Unilateral culture positivity was higher (60%) than bilateral culture positivity (40%).Conclusion: The absence of growth in majority of the samples is because of the sterile nature of the normal conjunctiva.J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 9-12